Paternal Tobacco Smoke Correlated to Offspring Asthma and Prenatal Epigenetic Programming - Wu, Chih-Chiang; Hsu, Te-Yao; Chang, Jen-Chieh; Ou, Chia-Yu; Kuo, Ho-Chang; Liu, Chieh-An; Wang, Chih-Lu; Chuang, Hau; Chen, Chie-Pein; Yang, Kuender D. (Frontiers in Genetics, 2019)
Rationale: Little is known about effects of paternal tobacco smoke (PTS) on the offspring’s asthma and its prenatal epigenetic programming. Objective: To investigate whether PTS exposure was associated with the offspring’s asthma and correlated to epigenetic CG methylation of potential tobacco-related immune genes: LMO2, GSTM1 or/and IL-10 genes. Measurements and Main Results: In a birth cohort of 1629 newborns, we measured exposure rates of PTS (23%) and maternal tobacco smoke (MTS, 0.2%), cord blood DNA methylation, infant respiratory tract infection, childhood DNA methylation and childhood allergic diseases. Infants with prenatal PTS exposure had a significantly higher risk of asthma by age of 6 than those without (p=0.026). The PTS exposure doses at 0, <20 and ≧20 cigarettes per day were significantly associated with the trend of childhood asthma and the increase of LMO2-E148 (p=0.006), and IL10_P325 (p=0.008) CG methylation. The combination of higher CG methylation levels of LMO2_E148, IL10_P325 and GSTM1_P266 corresponded to the highest risk of asthma by 43.48%, compared to other combinations (16.67%-23.08%) in the 3-way multi-factor dimensionality reduction (MDR) analysis. The LMO2_P794 and GSTM1_P266 CG methylation levels at age 0 were significantly correlated to those at age of 6. Conclusions: Prenatal PTS exposure increases CG methylation contents of immune genes, such as LMO2 and IL-10, which significantly retained from newborn stage to 6 years of age and correlated to development of childhood asthma. Modulation of the LMO2 and IL-10 CG methylation and/or their gene expression may provide a regimen for early prevention of PTS-associated childhood asthma.